Advanced Light Management for Encapsulated Silicon Solar Cells: An Antireflective Textured Film with a Down-Shifting Lead-free Perovskite Cs2AgxNa1-xBiyIn1-yCl6 Phosphor - Kong, Mengqin; Raievska, Oleksandra; Stroyuk, Oleksandr; Barabash, Anastasia; Wu, Zhenni; Tian, Jingjing; Erban, Christof; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Light management (LM) is the key to the encapsulation of high-performance silicon (Si) photovoltaic devices (PVs). In this work, simulation analyses provide meaningful insights into optical losses and guide the improvement of the PV performance of the encapsulated silicon solar cells (Encap-Si SCs). An antireflective layer, textured polydimethylsiloxane (PDMS), is designed to reduce reflection losses, especially at a lower illumination intensity, thereby achieving an improvement of 10.89% in the short-current density (JSC) and hence 12.67% in the power conversion efficiency (PCE) when illuminated at an incident angle of 60°. Subsequently, a luminescence down-shifting material, lead-free Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) double perovskite phosphor, is incorporated into the PDMS film to further enhance the energy yield in the ultraviolet (UV) region. The textured PDMS film with an optimized CANBIC content ultimately achieves a significant improvement in PCE from 21.770 to 23.136%. This enhancement is attributed to the increase in JSC by 2.381 mA/cm2 due to the reduced reflection losses (by antireflective PDMS) and down-converted UV energy (by CANBIC), providing a remarkable advance in LM toward highly efficient encapsulated PVs.
CRIS-Team Scopus Importer:2024-08-23
Keywords: antireflective layer; down-shifting layer; encapsulated Si solar cell; lead-free perovskite phosphor; optical simulation

Aerosol-Jet-Printed Silver Nanowires as Top Electrodes in Organic Photovoltaic Devices - Arango-Marín, Vanessa; Rocha-Ortiz, Juan S.; Osterrieder, Tobias; Barabash, Anastasia; Osvet, Andres; Wortmann, Jonas; Heumüller, Thomas; Liu, Chao; Hauch, Jens; Brabec, Christoph J. (Solar RRL, 2025)
Aerosol jet printing (AJP) is an effective method for manufacturing organic photovoltaic (OPV) devices for indoor use. Its noncontact deposition, without posttreatment, and high-resolution 3D pattern printing capabilities make it ideal for using functional nanomaterial inks. This study explores ultrasonic AJP (uAJP) atomization to deposit silver nanowires (AgNW) as the top electrode layer (TEL) in OPV devices. The OPV stack is fabricated up to the hole transport layer using high-throughput screening (HTS) methodologies. Different deposition techniques, including spin-coating, blade-coating, and uAJP of AgNW inks, as well as thermal evaporation of silver, are compared. Scanning electron microscopy analysis shows that the E2X AgNW ink formed a compact TEL layer. Combining HTS setups, right selection of interlayers and uAJP method, automated, solution-processed OPV devices with power conversion efficiencies of 9.54% on an active layer of 0.0232 cm2 are achieved, the highest reported for OPV devices using uAJP AgNW inks as top electrodes.
CRIS-Team Scopus Importer:2025-01-31
Keywords: aerosol jet printing; organic photovoltaics; ultrasonic spray coating

AgIn5S8/ZnS Quantum Dots for Luminescent Down-Shifting and Anti-Reflective Layer in Enhancing Photovoltaic Performance - Kong, Mengqin; Osvet, Andres; Barabash, Anastasia; Zhang, Kaicheng; Hu, Huiying; Elia, Jack; Erban, Christof; Yokosawa, Tadahiro; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2023)

A polymer bilayer hole transporting layer architecture for high-efficiency and stable organic solar cells - Xu, Junyi; Heumüller, Thomas; Le Corre, Vincent Marc; Barabash, Anastasia; Félix, Roberto; Frisch, Johannes; Bär, Marcus; Brabec, Christoph (Joule, 2024)
All-solution-processed organic photovoltaic (OPV) cells allow cost- and energy-effective fabrication methods for large-area devices. Despite significant progress on laboratory-scale devices, there is still a lack of interface materials that can be solution processed on top of the active layer, are compatible with novel non-fullerene acceptors (NFAs), and also provide sufficient long-term stability. We developed a novel interface layer concept, where alcohol-based organic polymer nanoparticles can be processed on top of a polymer-NFA active layer and doped to achieve a quasi-Ohmic hole contact. Moreover, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is processed as a second layer, forming a bilayer solution-processed hole transporting layer (HTL), providing an industrially relevant inverted architecture with a protective PEDOT:PSS layer on top. Most importantly, exceptional stability is observed. PM6:Y6 devices with the bilayer HTL are demonstrated to maintain 93% of their initial efficiency for 1,800 h under continuous solar cell operation at 60°C.
CRIS-Team Scopus Importer:2024-10-11
Keywords: hole transport layer; nanoparticles; organic solar cell; solution-processed

Band-bowing effects in lead-free double Cs2AgBixSb1−xCl6 perovskites and their anion-exchanged derivatives - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Hooper, Riley W.; Michaelis, Vladimir K.; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
Green synthesis of lead-free Cs2AgBixSb1−xCl6 solid-solution double perovskites and their conversion into bromide and iodide derivatives is reported. Interaction of the single-phase Cs2AgBixSb1−xCl6 double perovskites with sodium iodide in 2-propanol/glycerol yields Cs3Bi2xSb2(1−x)I9 derivatives with varied Bi/Sb ratio, while the similar anion exchange with sodium bromide results in mixtures of Cs3Bi2xSb2(1−x)Cl3Br6 and Cs2AgBixSb1−xCl2Br4. A band-bowing effect is revealed for the starting chloride perovskites and the anion-exchange products, with the indirect band gap of intermediate Bi/Sb mixed compounds being significantly lower than the band gaps of corresponding Bi- and Sb-pure products. Solid-state nuclear magnetic resonance spectroscopy uncovered that the band-bowing originates from the lattice disorder of mixed Bi/Sb halide compounds, thus highlighting a new approach for the bandgap design of halide perovskites.
CRIS-Team Scopus Importer:2024-12-16

Characterization of Aerosol Deposited Cesium Lead Tribromide Perovskite Films on Interdigited ITO Electrodes - These, Albert; Khansur, Neamul Hayet; Almora, Osbel; Luer, Larry; Matt, Gebhard; Eckstein, Udo; Barabash, Anastasia; Osvet, Andres; Webber, Kyle Grant; Brabec, Christoph (Advanced Electronic Materials, 2021)
Aerosol deposition (AD) is a promising additive manufacturing method to fabricate low-cost, scalable films at room temperature, but has not been considered for semiconductor processing, so far. The successful preparation of cesium lead tribromide (CsPbBr3) perovskite films on interdigitated indium tin oxide (ITO) electrodes by means of AD is reported here. The 20–35 µm thick layers are dense and have good adhesion to the substrate. The orthorhombic Pnma crystal structure of the precursor powder was retained during the deposition process with no signs of defect formation. The formation of electronic defects by photoluminescence spectroscopy is investigated and found slightly increased carrier recombination from defect sites for AD films compared to the powder. A nonuniform defect distribution across the layer, presumably induced by the impact of the semiconducting grains on the hard substrate surface, is revealed. The opto-electronic properties of AD processed semiconducting films is further tested by electrical measurements and confirmed good semiconducting properties and high responsivity for the films. These results demonstrate that AD processing of metal halide perovskites is possible for opto-electronic device manufacturing on 3D surfaces. It is believed that this work paves the way for the fabrication of previously unimaginable opto-electronic devices by additive manufacturing.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aerosol deposition; hysteresis; impedance spectroscopy; inorganic perovskites; photoluminescence spectroscopy

Composition-Dependent Optical Band Bowing, Vibrational, and Photochemical Behavior of Aqueous Glutathione-Capped (Cu, Ag)-In-S Quantum Dots - Raievska, Oleksandra; Stroyuk, Oleksandr; Azhniuk, Yuriy; Solonenko, Dmytro; Barabash, Anastasia; Brabec, Christoph; Zahn, Dietrich R. T. (Journal of Physical Chemistry C, 2020)
A mild aqueous synthesis of colloidal 2-4 nm (Cu, Ag)-In-S (CAIS) quantum dots (QDs) stabilized by surface metal complexes with glutathione was introduced. Linear variations of the interplanar distances as well as of the characteristic Ag(Cu)-S-related Raman vibrational frequencies of CAIS QDs with the increasing copper content show such QDs to be solid solutions rather than a mixture of AIS and CIS phases. At the same time, the band gaps and the energies of the photoluminescence (PL) band maxima of CAIS QDs show nonmonotonous changes decreasing from AIS to CAIS QDs (50 mol % Cu) and then increasing back for Cu-richer CAIS compositions and pure CIS. This behavior was interpreted as a result of the band bowing phenomenon. The bowing parameters of CAIS QDs determined from both absorption spectra (1.10 eV) and PL spectra (0.38 eV) are close to the range typically reported for ternary bulk MI-MIII-S compounds with the MI sites occupied by a mixture of copper and silver cations. The PL intensity of CAIS QDs was found to decrease during PL registration due to the photochemical decomposition of QDs, and the efficiency of this process increases with the increasing copper content. A similar trend was found in the photocatalytic reduction of methylviologen cations by hydrosulfide anions in the presence of CAIS. The initial rate of this reaction increased monotonously from AIS to CAIS to CIS QDs, with the activity of the CAIS QDs (50 mol % Cu) and pure CIS QDs being, respectively, 1.5 and 2.7 times higher than the photoactivity of pure AIS QDs. This trend is compliant with a strong decrease in the PL emission efficiency observed from AIS to CAIS to CIS QDs. Similar optical and photochemical properties were revealed for core/shell CAIS/ZnS QDs. The band bowing effect and photochemical activity of mixed CAIS (CAIS/ZnS) QDs open good perspectives for light-conversion applications in the photon energy range down to 1.8 eV.
CRIS-Team Scopus Importer:2020-10-23

Cs2AgxNa1-xBiyIn1-yCl6 perovskites approaching photoluminescence quantum yields of 100% - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Kupfer, Christian; Osvet, Andres; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Hauch, Jens; Brabec, Christoph J. (Materials Advances, 2022)
A new single-step and green approach for the synthesis of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites in ambient conditions is introduced. The CANBIC powders emit broadband self-trapped excitonic photoluminescence (PL) with a champion PL quantum yield (QY) of 98 +/- 2% and a PL lifetime of ca. 2 mu s observed for x = 0.40 and y = 0.01-0.02. The study focuses on the dependence of structural, spectral, and photophysical properties of CANBICs on Bi content. CANBICs are solid solutions with isomorphous In-to-Bi substitution with the bandgap and valence band edge energy decreasing gradually with increasing y. The PL QY and the rate constant of the radiative recombination showed volcano-shaped dependences on the Bi content, while the rate of the non-radiative recombination revealed a drastic growth by three orders of magnitude as the Bi fraction y was elevated from 0.01 to 1.0 indicating that BiCl6 units are responsible for non-radiative recombination.
CRIS-Team WoS Importer:2022-09-09

Doping of Mesoscopic Charge Extraction Layers Enables the Design of Long-Time Stable Organic Solar Cells - Xu, Junyi; Luo, Junsheng; Gubanov, Kirill; Barabash, Anastasia; Fink, Rainer; Heumüller, Thomas; Brabec, Christoph (ACS Energy Letters, 2024)
Realizing efficient and stable organic solar cells (OSCs) via all-solution processing requires the design of tailored charge extraction interfaces. Herein, we demonstrate a substantially different interface concept for OSC that is based on a low-temperature processed mesoscopic hole transporting layer (HTL) derived from partially covered organic nanoparticles (NPs) in the n-i-p structure. The mesoscopic interface is further doped in a second coating step with an organic salt dopant, BCF-Li. The interactions among the dopant, the solvent for sequential doping, and the semiconductor layer are surprisingly complex. The mesoscopic interface is necessary to evenly wet the semiconductor and prevent the aggregation of the dopant. At the same time, the sequential process reduces the excess acceptor at the interface. Both processes together are necessary to generate an efficiently doped interface for low-Ohmic-charge extraction and stable contacts. Devices with fully solution-processed mesoscopic interfaces show a superb shelf lifetime of over 22000 h without encapsulation and a long-term operational stability under 1 sun illumination for 2000 h (T80). Flexible devices bypass 1000 bending cycles with negligible degradation. Mesoscopic doped interfaces are demonstrated as an alternative to PEDOT:PSS as well as PEDOT related interface concepts for nonfullerene acceptors (NFA) in the n-i-p architecture.
CRIS-Team Scopus Importer:2024-01-12

Effect of Ligand Treatment on the Tuning of Infrared Plasmonic Indium Tin Oxide Nanocrystal Electrochromic Devices - Mashkov, Oleksandr; Körfer, Julien; Eigen, Andreas; Yousefi Amin, Amir-Abbas; Killilea, Niall Andrew; Barabash, Anastasia; Sytnyk, Mykhailo; Khansur, Neamul Hayet; Halik, Marcus; Webber, Kyle Grant; Heiß, Wolfgang (Advanced Engineering Materials, 2020)
Electrochromic devices operating in the near infrared are being developed as a part of smart windows that can dynamically modulate visible light and heat transmittance of solar irradiation, dependent on weather conditions and personal preferences. Here, doped metal oxide nanocrystals are used to obtain the desired effect in the infrared spectral region. Specifically, the infrared transmittance is electrochemically modulated by control of the carrier concentration in the nanocrystals. While indium tin oxide nanocrystals are already known to provide this effect, the consequence of ligand treatment during preparation of the nanocrystal electrode on the electrochromic properties is studied. The type of ligand treatment is shown to affect the surface morphology, as well as the localized plasmon resonance energy of the nanocrystal films. A short and convenient treatment by ethanedithiol cross-linking ligands is shown to provide superior results as compared with the formic acid treatment used in the previous work. Future work combining windows based on optimized electrochromic effects in the near infrared combined with those in the visible spectral range will simultaneously improve building energy efficiency and indoor human comfort.
CRIS-Team Scopus Importer:2020-05-02
Keywords: electrochromic windows; ligand exchange; localized surface plasmon resonances; metal oxide nanocrystals

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

Erratum: In(iii)-dictated formation of double Cs2AgxNa1−xFeyIn1−yCl6 perovskites (J. Mater. Chem. C (2023) 11 (6867–6873) DOI: 10.1039/D3TC01138) - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
The authors regret errors in Fig. 1(d) of the published article, in which the XRD patterns in Fig. 1(d) were incorrectly labelled with the In fraction values instead of the Fe fraction y values; in addition, the curves should have been numbered to correspond with the discussion in the main text. The corrected Fig. 1 image and caption are as shown here. (Figure Presented). The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
Created from Fastlane, Scopus look-up

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

"Green" synthesis of highly luminescent lead-free Cs2AgxNa1-xBiyIn1-yCl6 perovskites - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Batentschuk, Miroslaw; Osvet, Andres; Fiedler, Saskia; Resch-Genger, Ute; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2022)
A new "green" and mild synthesis of highly stable microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites under ambient conditions was developed that is scalable to the multi-gram production. Under UV illumination, the CANBIC perovskites emit intense broadband photoluminescence (PL) with a quantum yield (QY) of 92% observed for x = 0.35 and y = 0.01-0.02. The combination of strong UV absorbance and broadband visible emission, high PL QY, and long PL lifetimes of up to 1.4 mu s, along with an outstanding stability makes these CANBICs a promising material class for many optical applications.
CRIS-Team WoS Importer:2022-06-24

Highly Luminescent Transparent Cs2AgxNa1-xBiyIn1-yCl6 Perovskite Films Produced by Single-Source Vacuum Deposition - Stroyuk, Oleksandr; Raievska, Oleksandra; Sebastia-Luna, Paz; Huisman, Bas A.H.; Kupfer, Christian; Barabash, Anastasia; Hauch, Jens; Bolink, Henk J.; Brabec, Christoph J. (ACS Materials Letters, 2023)
Thermal deposition of halide perovskites as a universal and scalable route to transparent thin films becomes highly challenging in the case of lead-free double perovskites, requiring the evaporation dynamics of multiple metal halide sources to be balanced or a single-phase precursor preliminary synthesized to achieve a reliable control over the composition and the phase of the final films. In the present Letter, the feasibility of the single-source vacuum deposition of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 double perovskites into corresponding transparent nanocrystalline films while preserving the bulk spectral and structural properties is shown. The perovskite films produced from the most emissive powders with x = 0.40 and y = 0.01 revealed a photoluminescence quantum yield of 85%, highlighting thermal evaporation as a promising approach to functional perovskite-based optical materials.
CRIS-Team Scopus Importer:2023-02-03

Highly Stable Lasing from Solution-Epitaxially Grown Formamidinium-Lead-Bromide Micro-Resonators - Afify, Hany A.; Sytnyk, Mykhailo; Rehm, Viktor; Barabash, Anastasia; Mashkov, Oleksandr; Osvet, Andres; Volobuev, Valentine V.; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Götz, Klaus; Unruh, Tobias; et al. (Advanced Optical Materials, 2022)
High-quality epitaxial growth of oriented microcrystallites on a semiconductor substrate is demonstrated here for formamidinium lead bromide perovskite, by drop casting of precursor solutions in air. The microcrystallites exhibit green photoluminescence at room temperature, as well as lasing with low thresholds. Lasing is observed even though the substrate is fully opaque at the lasing wavelengths, and even though it has a higher refractive index as the perovskite active material. Moreover, the lasing is stable for more than 109 excitation pulses, which is more than what is previously achieved for devices kept in the air. Such highly stable lasing under pulsed excitation represents an important step towards continuous mode operation or even electrical excitation in future perovskite-based devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: halide perovskites; lasing; microresonators; solution epitaxy

High-Throughput Robotic Synthesis and Photoluminescence Characterization of Aqueous Multinary Copper–Silver Indium Chalcogenide Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Langner, Stefan; Kupfer, Christian; Barabash, Anastasia; Solonenko, Dmytro; Azhniuk, Yuriy; Hauch, Jens; Osvet, Andres; Batentschuk, Miroslaw; Zahn, Dietrich R. T.; Brabec, Christoph (Particle & Particle Systems Characterization, 2021)
The feasibility of a high-throughput robot-assisted synthesis of complex Cu1-xAgxInSySe1-x (CAISSe) quantum dots (QDs) by spontaneous alloying of aqueous glutathione-capped Ag–In–S, Cu–In–S, Ag–In–Se, and Cu–In–Se QDs is demonstrated. Both colloidal and thin-film core CAISSe and core/shell CAISSe/ZnS QDs are produced and studied by high-throughput semiautomated photoluminescence (PL) spectroscopy. The silver-copper-mixed QDs reveal clear evidence of a band bowing effect in the PL spectra and higher average PL lifetimes compared to the counterparts containing silver or copper only. The photophysical analysis of CAISSe and CAISSe/ZnS QDs indicates a composition-dependent character of the nonradiative recombination in QDs. The rate of this process is found to be lower for mixed copper-silver-based QDs compared to Cu- or Ag-only QDs. The combination of the band bowing effect and the suppressed nonradiative recombination of CAISSe QDs is beneficial for their applications in photovoltaics and photochemistry. The synergy of high-throughput robotic synthesis and a high-throughput characterization in this study is expected to grow into a self-learning synthetic platform for the production of metal chalcogenide QDs for light-harvesting, light-sensing, and light-emitting applications.
CRIS-Team Scopus Importer:2021-09-10
Keywords: combinatorial synthesis; semiconductor nanocrystals; spontaneous alloying; ternary chalcogenides; time-resolved photoluminescence

In(iii)-dictated formation of double Cs2AgxNa1−xFeyIn1−yCl6 perovskites - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2023)
Stable double Cs2AgxNa1−xFeyIn1−yCl6 (CANFIC) microcrystalline perovskites were produced in air-open conditions. In(iii) was found to steer the precursor interaction exclusively towards single-phase solid-solution CANFIC perovskite microcrystals with well-controlled composition, even when present at a small amount (1%). CANFICs revealed sensitivity in the visible range with the lowest bandgap of 1.95 eV found for y = 0.99. Due to a combination of open-environment synthesis conditions, reliable compositional control, the abundant and relatively non-toxic character of constituents, stability, and absorbance in the visible spectral range, CANFIC perovskites show high promises for photovoltaic and photochemical applications.
CRIS-Team Scopus Importer:2023-06-23

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Laser Cutting of Metal-Halide-Perovskite Wafers for X-Ray Detector Integration - Deumel, Sarah; Reg, Yvonne; Huerdler, Judith E.; Hussenether, Lukas; Schmidt, Oliver; Barabash, Anastasia; Heiß, Wolfgang; Tedde, Sandro F. (Advanced Materials Interfaces, 2022)
To realize various applications, structuring methods of metal-halide perovskites are of great importance. Most of the common techniques have focused on thin layers and suffer from limitations for thick layers. But thicknesses of several hundred micrometers are necessary, especially for the application field of medical X-ray detection. In order to scale perovskite-based X-ray detectors from small laboratory devices to realistic product sizes, new manufacturing strategies such as laser cutting are necessary. Here the potential of structuring any configurable geometry out of thick, freestanding methylammonium lead iodide (MAPbI3) wafers with ultrashort pulse (USP) laser at a wavelength of 1064 nm, is shown. A small difference in the laser parameters causes a significant variation of the perovskite from material decomposition to almost no effects. With the chosen parameter set of the USP laser, the MAPbI3 wafer can be shaped so that just slight changes in the morphology and no difference in the X-ray performance can be seen. This method offers the possibility of scaling up perovskite X-ray detectors in the future without significant signal loss.
CRIS-Team Scopus Importer:2022-05-06
Keywords: patterning; perovskites; structuring; ultrashort pulse laser; X-ray detection

Lead-Free Perovskite Cs2AgxNa1-xBiyIn1-yCl6 Microcrystals for Scattering-Fluorescent Luminescent Solar Concentrators - Kong, Mengqin; Osvet, Andres; Forberich, Karen; Barabash, Anastasia; Erban, Christof; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2025)
In recent years, luminescent solar concentrators (LSCs) have gained a renaissance as a pivotal transparent photovoltaic (PV) for building-integrated photovoltaics (BIPVs). However, most of the studies focused on light-selective LSCs, and less attention was paid to the utilization of the full solar spectrum. In this study, a lead-free microcrystal Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskite phosphor is demonstrated to have bifunctional effects of luminescent down-shifting (LDS) and light scattering for the fabrication of LSCs, realizing light response from ultraviolet (UV) to NIR regions by an edge-mounted Si solar cell. The optimized CANBIC content (30 mg) in an LSC realizes the best optical efficiency (ηopt) of 5.40% and an average visible transmission (AVT) of >50%. This contributes to the improvement in short circuit current density (JSC) up to 1.232 mA/cm2 for the LSC-PV system (one-edge mounted Si solar cell) as a result of the best power conversion efficiencies (PCEs) of 0.463% and 1.852% for the LSC-PV and LSC-4PV systems (four-edge mounted Si solar cells), respectively. An Al foil is applied as a reflection background in the LSC-4PV system, and a champion PCE of 3.14% is realized due to an improved JSC of up to 7.94 mA/cm2 in total. Furthermore, the LSC maintains superior stability under exposure to continuous ultraviolet illumination or in ambient air.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Cs; lead-free perovskite; light scattering; luminescent down-shifting; luminescent solar concentrator; photovoltaic

Ligand Tuning of Localized Surface Plasmon Resonances in Antimony-Doped Tin Oxide Nanocrystals - Balitskii, Olexiy; Mashkov, Oleksandr; Barabash, Anastasia; Rehm, Viktor; Afify, Hany A.; Li, Ning; Hammer, Maria; Brabec, Christoph; Eigen, Andreas; Halik, Marcus; Yarema, Olesya; Yarema, Maksym; et al. (Nanomaterials, 2022)
Aliovalent-doped metal oxide nanocrystals exhibiting localized surface plasmons (LSPRs) are applied in systems that require reflection/scattering/absorption in infrared and optical transparency in visible. Indium tin oxide (ITO) is currently leading the field, but indium resources are known to be very restricted. Antimony-doped tin oxide (ATO) is a cheap candidate to substitute the ITO, but it exhibits less advantageous electronic properties and limited control of the LSPRs. To date, LSPR tuning in ATO NCs has been achieved electrochemically and by aliovalent doping, with a significant decrease in doping efficiency with an increasing doping level. Here, we synthesize plasmonic ATO nanocrystals (NCs) via a solvothermal route and demonstrate ligand exchange to tune the LSPR energies. Attachment of ligands acting as Lewis acids and bases results in LSPR peak shifts with a doping efficiency overcoming those by aliovalent doping. Thus, this strategy is of potential interest for plasmon implementations, which are of potential interest for infrared upconversion, smart glazing, heat absorbers, or thermal barriers.
CRIS-Team WoS Importer:2022-10-28

Modified Synthesis of Cs4PbBr6 for Enhanced Purity and Quantum Yield and for Exploring Its Potential as a High Stokes Shift Material for Down-Conversion in Solar Cells - Darwish, Elshaimaa; Elia, Jack; Barabash, Anastasia; Hu, Huiying; Batentschuk, Miroslaw; Osvet, Andres (Advanced Engineering Materials, 2024)
Energy demands have kept increasing in recent years due to expanding human activity. Silicon solar cells offer an attractive renewable energy source while their external quantum efficiency (EQE) can still be enhanced; one way of doing this is by applying a photon energy downshifting layer. Herein, Cs4PbBr6 is applied as a downshifting layer; the Cs4PbBr6 is synthesized in the form of colloidal nanoparticles, and several modifications are introduced to the synthesis process, resulting in the enhancement of the photoluminescence quantum yield, improving the particle size distribution and reducing the CsBr impurities which appear as a side product during the synthesis of Cs4PbBr6. The application of the produced modified particles in the form of thin films on the top of Si solar cells shows an enhancement of the (EQE) of the solar cells when compared to the unmodified particles.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 0D Cesium lead halide; down conversion; enhancing quantum yield; perovskite nanoparticles; silicon solar cells

Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31

Over one-micron-thick void-free perovskite layers enable highly efficient and fully printed solar cells - Qiu, Shudi; Majewski, Martin; Dong, Lirong; Distler, Andreas; Li, Chaohui; Forberich, Karen; Tian, Jingjing; Hemasiri, Naveen Harindu; Liu, Chao; Zhang, Jiyun; Yang, Fu; Le Corre, Vincent Marc; et al. (Energy and Environmental Science, 2025)
Commercialization of perovskite photovoltaics hinges on the successful transition from laboratory-scale fabrication to industrial-scale manufacturing. A key challenge in fully printed perovskite solar cells with non-reflecting back electrodes is the deposition of high-quality, over-one-micron-thick perovskite layers to minimize photocurrent losses from incomplete light absorption. However, the formation of voids at the substrate/perovskite interface impedes the fabrication of such layers. Here, phase-field simulations reveal that the bottom voids originate from trapped residual solvents, driven by nanocrystal aggregation at the liquid-vapor interface during drying. Guided by these insights, we introduce a two-dimensional (2D) perovskite layer-assisted growth strategy to promote heterogeneous nucleation at the substrate, accelerating 3D perovskite crystallization and preventing solvent entrapment. This strategy enables the formation of highly crystalline, monolithic perovskite films exceeding one micrometer in thickness. The resulting void-free films maximize photocurrent extraction, achieving power conversion efficiencies of 19.9% on rigid substrates and 17.5% on flexible substrates in fully printed perovskite solar cells with non-reflecting carbon electrodes.
CRIS-Team Scopus Importer:2025-05-30

Polymer encapsulation impact on potential-induced degradation in PV modules revealed by a multi-modal field study - Buerhop, C.; Stroyuk, O.; Mashkov, O.; Barabash, Anastasia; Hauch, J. A.; Peters, I. M. (Solar Energy Materials and Solar Cells, 2024)
Potential-induced degradation is a significant issue affecting the performance and reliability of photovoltaic systems, particularly in large-scale installations. Understanding the mechanisms underlying the formation of potential-induced degradation is crucial for developing effective mitigation strategies and ensuring the long-term sustainability of solar energy technologies. During the inspection of a 1.2 MWp photovoltaic power plant, various imaging methods, electrical measurements, spectroscopic characterization methods, and monitoring data analyses were utilized and combined. We observed that two percent of the photovoltaic modules at the string ends exhibited the characteristic checkerboard pattern in infrared or electroluminescence imaging, implicating issues on twelve percent of all strings. This uneven distribution of potential-induced degradation-affected modules suggests additional key factors are at play. Investigations of the backsheet and ethylene-vinyl acetate using near-infrared reflectance analysis revealed that one backsheet type and two different ethylene-vinyl acetate types were present in the installed solar panels. Yet, only one type of ethylene-vinyl acetate correlated with potential-induced degradation. The same type also exhibited a higher rate of oxidative degradation. Scanning electron microscopy and energy-dispersive X-ray spectroscopy revealed a significantly increased sodium ion content in the ethylene-vinyl acetate and glass of the potential-induced degradation-affected modules. Our findings highlight the crucial role of polymer encapsulation in the development of potential-induced degradation and underscore the importance of careful polymer selection in the design of photovoltaic module technologies.
CRIS-Team Scopus Importer:2024-09-06

Precise control of process parameters for >23% efficiency perovskite solar cells in ambient air using an automated device acceleration platform - Zhang, Jiyun; Wu, Jianchang; Barabash, Anastasia; Du, Tian; Qiu, Shudi; Le Corre, Vincent Marc; Zhao, Yicheng; Zhang, Kaicheng; Schmitt, Frederik; Peng, Zijian; Tian, Jingjing; Li, Chaohui; et al. (Energy and Environmental Science, 2024)
Achieving high-performance perovskite photovoltaics, especially in ambient air, is critically dependent on the precise optimization of process parameters. However, traditional manual methods often struggle to effectively control the key variables. This inherent challenge requires a paradigm shift toward automated platforms capable of precise and reproducible experiments. Herein, we use a fully automated device acceleration platform (DAP) to optimize air-processed parameters for preparing perovskite devices using a two-step sequential deposition technique. Over ten process parameters with significant potential to influence device performance are systematically optimized. Specifically, we delve into the impact of the dripping speed of organic ammonium halide, a parameter that is difficult to control manually, on both perovskite film and device performance. Through the targeted design of experiments, we reveal that the dripping speed significantly affects device performance primarily by adjusting the residual PbI2 content in the films. We find that optimal dripping speeds, such as 50 µL s−1, contribute to top-performance devices. Conversely, excessively fast or slow speeds result in devices with comparatively poorer performance and lower reproducibility. The optimized parameter set enables us to establish a standard operation procedure (SOP) for additive-free perovskite processing in ambient conditions, which yield devices with efficiencies surpassing 23%, satisfactory reproducibility, and state-of-the-art photo-thermal stability. This research underscores the importance of understanding the causality of process parameters in enhancing perovskite photovoltaic performance. Furthermore, our study highlights the pivotal role of automated platforms in discovering innovative workflows and accelerating the development of high-performing perovskite photovoltaic technologies.
CRIS-Team Scopus Importer:2024-07-19

Revealing the Crystallization and Thermal-Induced Phase Evolution in Aromatic-Based Quasi-2D Perovskites Using a Robot-Based Platform - Zhang, Jiyun; Wu, Jianchang; Zhao, Yicheng; Zou, Yuqin; Barabash, Anastasia; Wu, Zhenni; Zhang, Kaicheng; Deng, Can; Elia, Jack; Li, Chaohui; Rocha Ortiz, Juan Sebastian; Liu, Chao; et al. (ACS Energy Letters, 2023)
Introducing large organic cations to form reduced-dimensional (quasi-2D) perovskites has proven to be effective in stabilizing three-dimensional perovskites. In this study, we synthesized 28 Ruddlesden-Popper-type quasi-2D perovskites using four aromatic-based cations (phenylmethylammonium (PMA), phenethylammonium (PEA), phenylpropylammonium (PPA), and phenylbutanammonium (PBA)) and systematically investigated their optoelectronic and structural properties and thermal stability. A counterintuitive finding that longer-chain PPA-based films exhibited relatively poorer stability compared to films with shorter-chain cations has been found. This instability in PPA-based samples is attributed to significant lattice distortion and a mismatched phase between face-sharing trimers, causing intense configurational strain. On the other hand, PBA-containing films maintained robust structural stability due to distinctive crystallization kinetics and a gradual phase-transformation process (from larger-n to lower-n phases) induced by a stronger steric-hindrance effect. Our study sheds light on the complex impact of aromatic-based cations on optoelectronic properties and stability of perovskites, providing guidelines for the rational compositional design engineering of highly stable perovskite material

Shape-Controlled Solution-Epitaxial Perovskite Micro-Crystal Lasers Rivaling Vapor Deposited Ones - Afify, Hany A.; Rehm, Viktor; Barabash, Anastasia; These, Albert; Zhang, Jiyun; Osvet, Andres; Schüßlbauer, Christoph; Thiel, Dominik; Ullrich, Tobias; Dierner, Martin; Przybilla, Thomas; Will, Johannes; et al. (Advanced Functional Materials, 2022)
Epitaxial growth methods usually need dedicated equipment, high energy consumption to maintain pure vacuum conditions and evaporation of source materials, and elevated substrate temperatures. Solution epitaxial growth requires nothing of that but is rarely used because the achieved microstructures are of low quality, not homogeneous, and finally exhibit worse performances in devices. Here, an antisolvent-vapor-assisted-crystallization of metal-halide-perovskites as a method overcoming these disadvantages is demonstrated. The methylammonium lead tribromide exhibits van-der-Waals type of epitaxial growth on mica substrates, resulting in micro-crystallites whose shape can be controlled to be either triangular micro-prism or micro-cuboid. These micro-crystallites act as optical resonators supporting various optical modes and lasing is achieved under optical excitation with low thresholds and record high environmental stability. Selecting suitable resonators from a large variety of sizes allows control of mode spacing and finally mono-mode operation, considered to be an important feature of semiconductor laser devices. The achieved results are essentially competitive to those obtained by vapor phase epitaxial microstructures, highlighting that epitaxy of high-quality optoelectronic device structures is feasible by minimum technological efforts and energy consumption, which are of increasing importance considering issues such as global warming and the current energy crisis.
Created from Fastlane, WoS look-up

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Tailoring doped organic nanoparticles as selective hole transporters for printed non-fullerene organic solar cells - Xu, Junyi; Späth, Andreas; Gruber, Wolfgang; Barabash, Anastasia; Stadler, Philipp; Gubanov, Kirill; Wu, Mingjian; Forberich, Karen; Spiecker, Erdmann; Fink, Rainer H.; Unruh, Tobias; McCulloch, Iain; et al. (Nano Energy, 2023)
Keywords: Inverted structure; Organic nanoparticle; Doping; Organic solar cell; Solution-processed hole transporting layer

Unveiling the Role of BODIPY Dyes as Small-Molecule Hole Transport Material in Inverted Planar Perovskite Solar Cells - Seoneray, Isabel; Wu, Jianchang; Rocha-Ortiz, Juan S.; Bornschlegl, Andreas; Barabash, Anastasia; Wang, Yunuo; Lüer, Larry; Hauch, Jens; García, Angélica; Zapata-Rivera, Jhon; Brabec, Christoph J.; Ortiz, Alejandro (Solar RRL, 2024)
Perovskite solar cells (PSCs) have become a research hotspot since their dramatic increase in power conversion efficiency (PCE), surpassing 26% due to advances in cell engineering and interfacial layers. Within the last factor, hole transporting materials play a crucial role in enhancing device performance and stability. Among several molecular building blocks, BODIPYs are attractive for the design of novel hole transporting material (HTMs) due to their outstanding photophysical and charge transport properties easily tuned by synthetic modifications. Herein, the synthesis of five new BODIPY-based HTMs PyBDP 1–5 are reported, functionalized at the meso- and α- positions with pyrenyl and arylamino units, respectively. The resulting compounds exhibit broad absorption in the visible region, remarkable thermal stability, narrow bandgaps, suitable energy levels, and good hole extraction capability, as subtracted from experimental and computational characterizations. The performance of the BODIPY derivatives as HTMs is evaluated in planar inverted (p-i-n) PSCs and compared to commonly used PTAA, resulting in highly efficient systems, reaching PCEs very close to that obtained with the reference polymer (21.51%). The incorporation of these BODIPY-based HTMs result in an outstanding PCE of 20.37% for devices including PyBDP-1 and 19.97% for devises containing PyBDP-3, thus demonstrating that BODIPY derivatives are a promising alternative to obtain simple and efficient organic HTMs.
CRIS-Team Scopus Importer:2024-05-31
Keywords: arylamine; BODIPY; hole-transporting material; perovskite solar cells; pyrene